Evaluating the Effectiveness of DOLE Integrated Livelihood Program (DILP) to Group Beneficiaries of Livelihood Funds from 2020 to 2021 in Cebu Province - Davis III, Rafael D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study evaluates the implementation and effectiveness of the Department of Labor and Employment Integrated Livelihood Program (DILP) in Cebu Province, Philippines, focusing on its impact on beneficiaries. Anchored by the Sustainable Livelihood Framework (SLF) by Robert Chambers and Gordon Conway, this theory posits that enhancing various forms of capital can lead to improved livelihood outcomes, such as increased income and employment. Descriptive-observational analysis and qualitative approach were employed using questionnaire to collect both quantitative and qualitative data from 201 beneficiaries through cluster sampling of the workers associations. The study assessed the program's effectiveness based on program coverage, business capital, income, economic stability, type of employment, and employment security. Findings revealed that DILP positively impacted beneficiaries' income and employment. Recommendations include the development of targeted enrichment programs in areas such as entrepreneurship, marketing, management, and financial planning to effectively strengthen livelihood assets and contribute to sustainable socio-economic status. This study provides significant insights for policymakers, program implementers, and local government units (LGUs) to refine strategies, optimize resource allocation, and foster community development. The findings offered a foundation for future comparative studies in public administration and socio-economic research. However, this study is limited only to the livelihood funds released from 2020 to 2021.